THE INFLUENCE OF ECONOMICS GROWTH, MINIMUM WAGES, POVERTY AND CAPITAL EXPENDITURES ON THE HDI - Anisa Nur Hestiningsih; Izza Mafruhah; Chenny Seftarita (MESP–FEB UNS, 2023)
This study aims to analyze the influences of economic growth, minimum wages, poverty and capital expenditure to the Human Development Index in Ex-Residency of Surakarta and to analyze the regional classification based on the Klassen Typology. Data analysis method used is panel data regression with Random Effect Model and Klassen Typology. The time period of this study is eight years from 2011 to 2018. Panel data regression results show that economic growth, minimum wages, and capital expenditure have a positive and significant effect on the HDI. Poverty has a negative and significant effect on the HDI. Based on the Klassen Typology according to income per capita and economic growth, Ex-Residency of Surakarta divided into three regional quadrants. Meanwhile according to the HDI and economic growth, Ex-Residency of Surakarta divided into four regional quadrants. Regional classification according to the Klassen Typology which is based on HDI and economic growth in 2011 shows that (1) Surakarta, Sukoharjo and Klaten are developed regions; (2) Karanganyar is a developed but depressed area; (3) Boyolali and Sragen are developing areas; and (4) Wonogiri is a disadvantaged area. Meanwhile, 2018 showed changes that saw Karanganyar become a developed region category; Klaten is categorized as a developed but depressed area; and other districts/cities still remain in the same category as in 2011. This shift occurred due to changes in human development and economic growth in cities and districts in the former Surakarta Residency.